Abastecimiento de agua potable del distrito de Barranquita - Reyna Flores, Carlos Nicolás (2003)
The thesis project called "WATER SUPPLY DISTRICT POT A8LE Barranquita" arises from the need to solve one of the major problems that directly affects the health of the population of Barranquita; so that within this social contex1o has developed this work with the main objective to contribute to solving this problem by providing an essential basic service. This work raises capture water from the only source capable of supplying by gravity and this Negroyacu Gulch; led to the treatment plant it consists of a distribution box of flows, four clarifiers, four slow filters a collection box filtered water and a circular reservoir 250 m. Through the gate valves are regulated in food distribution networks to finally provide them with domiciliary facilities to all beneficiaries. To better study it has been divided into chapters VI distributed as follows: In Chapter 1 e: situational analysis puts the district Barranquita, considering the geopolitical, demographic and socio-economic characteristics, basic data also hydrology, soils, topography and engineering of the project, information that will allow us to raise the theoretical framework the project finally justification, scope, limitations, goals and assumptions expressed; In Chapter 11 refers the materials and methods used accurately and concisely; In Chapter 111 talking about the results for which the most suitable alternative was selected from the technical, social and economic terms; In Chapter IV the results obtained in the previous chapter is analyzed in Chapter V look at the conclusions that were reached after getting the final results finally in Chapter VI relevant recommendations set out to improve the maintenance and system operation being carried out for this project.